2018
DOI: 10.18203/2319-2003.ijbcp20184866
|View full text |Cite
|
Sign up to set email alerts
|

Piperacillin-tazobactam induced hypokalaemia

Abstract: Electrolytes imbalance has been reported with the use of several antimicrobials in clinical scenarios. Piperacillin/tazobactam is a commonly used antibiotic with tolerable side effects and broad antimicrobial activity in general practice. Herein we report a case of a 27 year old male presented with Road Traffic Accident with depressed frontal bone fracture, fracture humerus and fracture of great toe complicated with Ventilator associated Pneumonia (VAP) who developed hypokalemia secondary to intravenous pipera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Another retrospective study by Kuramoto et al [18] assessing the incidence and risk factors of TAH reported a much higher incidence of 24.8%. In addition, serious TAH cases, mostly accompanied by arrhythmia and treatment discontinuation, Antibiotics 2022, 11, 1138 2 of 9 have been continuously reported [19][20][21][22][23][24][25]. Nevertheless, the risk factors of TAH have not been well known because of the lack of related studies.…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective study by Kuramoto et al [18] assessing the incidence and risk factors of TAH reported a much higher incidence of 24.8%. In addition, serious TAH cases, mostly accompanied by arrhythmia and treatment discontinuation, Antibiotics 2022, 11, 1138 2 of 9 have been continuously reported [19][20][21][22][23][24][25]. Nevertheless, the risk factors of TAH have not been well known because of the lack of related studies.…”
Section: Introductionmentioning
confidence: 99%